Effect of waterlogging on seed germination and growth of selected tree species in Dharabi watershed, district Chakwal (Zoo Botanica, 2025)
The purpose of this research in the Dharabi watershed region was to investigate the seed germination and growth potential of selected (04) tree species (Ziziphus mauritiana, Melia azedarach, Acacia modesta, Acacia nilotica). The study was conducted to identify the effect of waterlogging on seed germination and growth of selected species that can develop at the fastest pace under waterlogging stress. The research was based on Pot experiments and field experiments. Four treatments (T0, T1, T2, and T3) were utilized, and germination and mortality percentages were investigated. Growth parameters consisted of height, stem diameter, and leaf number. The data was analyzed using CRD (Complete Random Design) and R Studio for Windows, using a statistical test (ANOVA). The results showed that the means of significant effects were separated using the LSD at a 5% probability. Being planted in waterlogged environments, Acacia nilotica had the highest average percentage of seed germination out of selected species, regardless of the degree of waterlogging stress that was applied. In comparison to other species, the Acacia nilotica plant's height was noticeably greater and had a significantly larger stem diameter. Ziziphus mauritiana also progressed very well; however, the results produced by Acacia modesta were unsatisfactory. These results will help in the plantation of the best-suited plants in the waterlogged areas in the future.
Keywords: Acacia nilotica; Acacia modesta; Melia azedarach; Ziziphus mauritiana; growth potential; mortality percentage; waterlogging tolerance